SPE Annual Technical Conference and Exhibition 2005
DOI: 10.2118/96879-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Unconventional Resource Plays

Abstract: Making sound business decisions in one of the hottest domestic exploration plays, unconventional gas, offers a set of challenges not usually encountered with more traditional opportunities. Unlike with standard prospect and conventional play risk analysis, geologic chance is not a major issue, and estimates of initial production, decline rates, mechanical efficiency, and success planning dominate the analysis rather than traditional volumetric determinations. The valuation and assessment of unconventional or "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…There has not been a comprehensive model for planning the exploration and evaluation of a CBM play. A number of authors have addressed to some degree of detail individual phases of the assessment process for CBM while only briefly touching on the other pre-or post-phases in the assessment process (Puri et al 1995;Blauch et al 2002;Green et al 2003;Haskett and Brown 2005;Weida et al 2005;Rodvelt and Oestreich 2005;Clarkson and McGovern 2005). The aim of this paper is to develop a morecomplete, -consistent, and -accepted approach to the evaluation of CBM opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…There has not been a comprehensive model for planning the exploration and evaluation of a CBM play. A number of authors have addressed to some degree of detail individual phases of the assessment process for CBM while only briefly touching on the other pre-or post-phases in the assessment process (Puri et al 1995;Blauch et al 2002;Green et al 2003;Haskett and Brown 2005;Weida et al 2005;Rodvelt and Oestreich 2005;Clarkson and McGovern 2005). The aim of this paper is to develop a morecomplete, -consistent, and -accepted approach to the evaluation of CBM opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…These results should be compared to approach developed by Haskett and Brown (Haskett and Brown, 2005). While Haskett and Brown do not present these charts we can calculate them from their Figure 16.…”
Section: Illustrative Examplementioning
confidence: 99%
“…These include Gray et al (2007), Stabell et al (2007), Gouveia et al (2009), Williams-Kovacs and Clarkson (2011), Giles et al (2012), Ingsoy et al (2013), and Allan (2013). Haskett and Brown (2005), Willigers et al (2014), and Bickel (2014) demonstrated how the initial view of the projected well performance in a reservoir can be revised using Bayes' rule as new data come to light by applying the general principles developed by Schlaifer (1959) over fifty years ago.…”
Section: Introductionmentioning
confidence: 99%
“…The total set of production data gathered from wells that were drilled in different phases of an appraisal programme should be used in the assessment of the reservoir. Hence, the reliability of an appraisal programme is determined not solely by the number of pilot wells (Haskett and Brown, 2005;Bickel, 2014) but also by the length of time the wells have been produced.…”
Section: Introductionmentioning
confidence: 99%